2019
DOI: 10.1073/pnas.1911892116
|View full text |Cite|
|
Sign up to set email alerts
|

Salicylic acid-mediated plasmodesmal closure via Remorin-dependent lipid organization

Abstract: Plasmodesmata (PD) are plant-specific membrane-lined channels that create cytoplasmic and membrane continuities between adjacent cells, thereby facilitating cell–cell communication and virus movement. Plant cells have evolved diverse mechanisms to regulate PD plasticity in response to numerous environmental stimuli. In particular, during defense against plant pathogens, the defense hormone, salicylic acid (SA), plays a crucial role in the regulation of PD permeability in a callose-dependent manner. Here, we un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(153 citation statements)
references
References 57 publications
(79 reference statements)
10
141
1
1
Order By: Relevance
“…This beneficial effect could be due to the protective role of SA, yeast, and proline in plasma membrane stability and increasing soluble metabolite accumulation. A similar result was indicated by Ishikawa and Evans [56] and Huang et al [57], who reported that osmoregulators improve plant growth and yield under various stress conditions.…”
Section: Discussionsupporting
confidence: 86%
“…This beneficial effect could be due to the protective role of SA, yeast, and proline in plasma membrane stability and increasing soluble metabolite accumulation. A similar result was indicated by Ishikawa and Evans [56] and Huang et al [57], who reported that osmoregulators improve plant growth and yield under various stress conditions.…”
Section: Discussionsupporting
confidence: 86%
“…We, therefore, tested whether the increased sterol content could explain the DSF-induced phenotypes by treating Arabidopsis seedlings with Methyl-β-cyclodextrin (MβCD) in combination with DSF. MβCD is a widely used sterol-depleting agent that acts strictly at the membrane surface by binding to sterol with high affinity and remove sterol acutely within minutes, with demonstrated success in acute depletion of sterols in both plant and animal cells ( López et al, 2011 ; Gerbeau-Pissot et al, 2014 ; Valitova et al, 2014 ; Mahammad & Parmryd, 2015 ; Huang et al, 2019 ). Here, we found that MβCD fully blocked the DSF-induced inhibition of primary roots and root hairs, suggesting DSF’s opposite effects compared with MβCD on sterol perturbation in Arabidopsis .…”
Section: Resultsmentioning
confidence: 99%
“…Analyses were conducted using an Exion ultra performance liquid chromatography (UPLC) (AB Sciex, CA, USA), coupled with Sciex QTRAP 6500 PLUS (AB Sciex, CA, USA), as reported previously [ 30 ]. Lipids were separated using a Phenomenex Luna 3 μm-silica column (Phenomenex, CA, USA) (internal diameter 150 × 2.0 mm) under the following conditions: mobile phase A (chloroform: methanol: ammonium hydroxide, 89.5:10:0.5) and mobile phase B (chloroform: methanol: ammonium hydroxide: water, 55:39: 0.5:5.5).…”
Section: Methodsmentioning
confidence: 99%